CHANGES IN WOMEN’S PROTRAYAL IN ADVERTISEMENT - Ajeera binti Paiz; Seri Rianri Mohd Isman (Proceedings Education and Language International Conference, 2017)
In this paper, the authors intend to investigate how women have been exploited in the world of mass media, particularly in this study, the advertising field. Numerous studies have surfaced in the past concerning this above issue, where researchers have published their statistics on the treatment of women in advertisements, which is by exploiting superficial qualities or characteristics of the female gender, merely for chasing profits and increasing value to male audiences. Common conscience would see that this is something which is shameful and should eventually be stopped. The society, as a whole, desperately needs to push for portrayal of women in advertisements to be more ethical, account for higher moral standards and help young women discover their talents, while rightfully receiving the recognition they deserve. From the findings of interviews conducted to a sample of respondents in Malaysia, it has been able to provide a localized perspective of this issue. Its findings serve to inform on the progress of women’s portrayal in Malaysia’s media. Also in the study, the authors will peg these issues surrounding women treatment to how a reform towards our education system can become a major step towards the obliteration of negative treatment of women in their careers.Keywords: exploitation, implications to education system, portrayal of women